Analisis pendapatan pedagang kaki lima di kawasan wisata Water Front City Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat - Pratiningsih Pratiningsih; Siti Hodijah; Candra Mustika (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the socio-economic characteristics of street vendors and analyze the income of street vendors in the Water Front City tourist area, Tungkal Ilir District, Tanjung Jabung Barat Regency. The data used in this study are primary data obtained using field research sourced from street vendors in the Water Front City tourist area as a sample. The sampling method used in this study is Stratified Random Sampling. The data were analyzed using descriptive qualitative and quantitative descriptive analysis methods. The results of the study found that the socio-economic characteristics of street vendors in the Water Front City tourist area were based on gender, age, education level, number of family members, work experience, and income. Based on the results of data processing, the income of street vendors will increase obtained from the regression coefficient of the venture capital variable of 1.080051 which has a significant effect on the income of street vendors with a probability level below 5% (0.05). While the variable working hours of 68927.75 and length of business of 169676.8 has no significant effect on the income of street vendors in the Water Front City tourist area, Tungkal Ilir District, Tanjung Jabung Barat Regency. Keywords: Income, Socio-economic characteristics of street vendors, Multiple linier regression analysis.